(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article discusses the possibilities of using enzyme preparations for disorders of the pancreas and gastrointestinal motility in childhood. In addition, the authors draw the reader’s attention to the possible causes of disorders, clinical manifestations and basic diagnostic methods for this pathology.